Analisis Semiotik Elemen Arsitektur Islam pada Rumah Adat Komering: Studi Terhadap Rumah Carahulu - Iskandar Iskandar; Akhmad Hamdi Asysyauki; Sisca Novia Angrini; Anson Ferdiant Diem (Universitas Muhammadiyah Palembang, 2024)
This study explores the architecture of Rumah Carahulu Komeryng, a form of vernacular house in South Sumatra Province. The Carahulu House not only functions as a place to live, but also as a center of social, cultural and religious life for the Komering Tribe community. This study uses a qualitative method with a semiotic approach to understand the meaning of the architectural elements of Rumah Carahulu in an Islamic perspective. The results of the study show that architectural elements such as the shape of the roof, space, main door, main window and ornaments have a deep symbolic meaning. The shape of the roof symbolizes the upper world as the ancestral residence and relationship with God. The separation of space between men and women reflects the principles of purity and honor in Islam. The main door facing the Qibla and decorated with Arabic calligraphy shows a spiritual orientation and openness to the teachings of Islam. The main window with Islamic ornaments depicts openness and transparency in religious life. Calligraphy ornaments and flora motifs contain profound moral and philosophical messages. This study concludes that the architecture of Rumah Carahulu Komering integrally incorporates Islamic values in its design and function, reflecting the life philosophy of the Komering community which adheres to the teachings of Islam.